Optimal replacement age of a conventional cotton harvester system. Issue 1 (29th April 2014) - Ibendahl, Gregory; Farrell, Matthew; Spurlock, Stan; Tack, Jesse
Abstract : Purpose: – The cotton industry has seen many technological advances throughout history that have greatly decreased the number of labor hours required to produce a bale of cotton. The latest advancement is a harvesting system that replaces the harvester, boll buggy, and module builder with a single machine. This is an asset replacement decision where there are multiple assets being replaced but the old technology (the defender assets) may all have different remaining lives and optimal lifespans. The purpose of this paper is to find the optimal time to replace the multiple defender assets with a single challenger asset (the improved technology). The goal is to determine if the ages of the boll buggy and the module builder affect the replacement age of the conventional picker. Design/methodology/approach: – The paper extends the Perrin model to allow for multiple defender assets. Findings: – The paper finds that the supporting assets do sometimes affect the decision to replace a conventional cotton picker. If the supporting assets are newer, then the replacement decision may be delayed and if the supporting assets are older then the replacement decision may be accelerated. Field efficiency can affect the decision as well. Originality/value: – While the Perrin model has been used extensively, the authors believe the application to a multiple asset defender is unique. Although this type of replacement decision is not common, there could be other applications as new technology is introduced on the farm.